Persepsi Manfaat Micro Teaching Terhadap Peningkatan Kompetensi Guru Dalam Aspek Pedagogik dan Kepribadian Pada Mahasiswa KKN STKIP Babunnajah - Irfan Bahtiar; Teguh Ardianto; Andri Imam Subekhi (Metakognisi, 2022)
The purpose of this article is to analyze the effect of student perceptions of the role of micro teaching courses on student teaching readiness. This type of research is descriptive quantitative. The population in this study were students of STKIP Babunnajah Pandeglang batch 2018 who had completed micro teaching and the Education Field Experience Program course with a total of 26 people. The sampling technique was purposive random sampling. Research data is primary data collected by questionnaire distributed via google form. The data were analyzed by descriptive analysis assisted by SPSS software. The results showed that STKIP Babunnajah Pandeglang students had a high perception of micro teaching learning in supporting the ability of pedagogic aspects and personality aspects with a perception value of 4.32 in the pedagogic aspect and 4.5 in the personality aspect.